Health risk assessment of drinking groundwater in rural areas of Ru village and surrounding areas in Wutai County, China - Qifa Sun; Lin Guo; Chen Hu; Tao Liu; Jingyao Sun; Long Zhou (Journal of Water and Health, 2024)
Nitrate pollution in groundwater is a global environmental problem that poses risks to human health. We investigate the health risks of nitrate in rural drinking groundwater in Rucun Township and surrounding areas of Wutai County, and provide a basis for healthy drinking water. By using statistical analysis software (SPSS19) and hydrogeochemical analysis software (AqQA), a qualitative and quantitative evaluation of nitrate health risks was conducted among populations of different ages and genders through water sample collection, chemical analysis, and construction of a human health risk model (HHRA). Through research, it was found that the average concentration of nitrate in the study area is 43.99 mg/L. Groundwater is severely polluted by NO3−, and nitrate pollution areas are mainly concentrated in the main human activity areas, especially in the main agricultural production areas. The Quaternary loess layer, as a permeable layer, cannot prevent groundwater from being polluted by NO3−. Through evaluation, it is believed that there is a health risk of nitrate pollution in rural drinking groundwater in Rucun Township and surrounding areas. Health risk level: infants>children>adult females>adult males. The discovery and evaluation results can provide a basis for the prevention and control of nitrate pollution in groundwater. HIGHLIGHTS This study determined the distribution pattern of nitrate in rural drinking groundwater in Rucun Township and surrounding areas.; The chemical characteristics of groundwater in the study area were reflected and described through the Durov diagram.; HHRA for the first time in Rucun Township and surrounding areas was established to assess the level of health risks in the study area.;